Respuesta :

Answer:

a = 2 , b = 6

Step-by-step explanation:

We require to express the 3 terms with a common denominator

The common denominator is (x + 1)(x - 1) = x² - 1, then

[tex]\frac{2(x^2-1)-(x-1)(x+3)-(x+1)(x-5)}{x^2-1}[/tex] ← distribute parenthesis on numerator

= [tex]\frac{2x^2-2-(x^2+2x-3)-(x^2-4x-5)}{x^2-1}[/tex]

= [tex]\frac{2x^2-2-x^2-2x+3-x^2+4x+5}{x^2-1}[/tex] ← collect like terms on numerator

= [tex]\frac{2x+6}{x^2-1}[/tex] ← in the form [tex]\frac{ax+b}{x^2-1}[/tex]

with a = 2 and b = 6